PERAN GURU DALAM MENGATASI PROBLEMATIKA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS KITAB KUNING DI SEKOLAH FORMAL (STUDI KASUS MTS. ALWASHLIYAH ISMAILIYAH MEDAN) - Affan Alhammam, Ahmad; Akrim, Akrim; Harfiani, Rizka (Berajah Journal, 2025)
The issue of Islamic Religious Education (PAI) learning based on the yellow book at MTs. Alwashliyah Ismailiyah Medan is influenced by students who are not madrasa graduates, causing difficulties and unfamiliarity in understanding the yellow book. Additionally, students' lack of interest in studying the yellow book also impacts the success of the learning process. This study aims to examine the role of teachers in addressing these challenges so that the learning process can run effectively. The research uses a qualitative method with a location at MTs. Alwashliyah Ismailiyah Medan. Primary data sources include three Islamic Religious Education teachers based on the yellow book and the head of the curriculum department, while secondary data is gathered from the principal and students. Data collection was conducted through interviews, observation, and documentation. The results show that teachers play a significant role in overcoming these issues through various approaches, such as building cooperation with homeroom teachers and other teachers to integrate other subjects with the yellow book. This helps students who do not have a madrasa background to understand and identify Arabic sentences, while also enhancing the abilities of students with a madrasa background in understanding the concepts of Islamic education using the yellow book as teaching material.